Prognostic significance of the presence of tertiary Gleason grade 5 in robot-assisted radical prostatectomy specimens in Japanese patients with clinically localized prostate cancer. (11th January 2019) - Kamoda, Naohiro; Ohori, Makoto; Hirasawa, Yosuke; Inoue, Rie; Hashimoto, Takeshi; Satake, Naoya; Gondo, Tatsuo; Nakagami, Yoshihiro; Nagao, Toshitaka; Ohno, Yoshio
Abstract : The presence of tertiary Gleason grade 5 in radical prostatectomy (RP) specimens is not a significant and independent predictor of biochemical recurrence after robot-assisted RP. Abstract: Background: The aim of this study was to study the prognostic significance of tertiary Gleason grade (TGG) 5 in patients with clinically localized prostate cancer treated with robot-assisted radical prostatectomy (RARP). Methods: A total of 600 Japanese patients who underwent RARP for clinical stage T1-3N0M0 prostate cancer were evaluated. TGG5 was evaluated according to the International Society of Urological Pathology criterion. Cox hazard regression was used to evaluate the prognostic significance of prostate-specific antigen and pathological features in RARP specimens. Results: Of the 600 RARP specimens, 92 (15%) had TGG5. TGG5 component was found in 30 (10%) of 287 cases with Gleason score (GS) 3 + 4, 55 (37%) of 149 cases with GS 4 + 3 and 7 (17%) of 40 cases with GS 4 + 4. There were no significant differences in pathological stage and surgical margin status between GS 3 + 4 with and without TGG5, as well as between GS 4 + 4 with and without TGG5. Of the 600 patients, 92 (15%) patients had biochemical recurrence (BCR) after surgery, with a median follow-up period of 42 (3–104) months. There were no differences in 5-year BCR-free survival rates between patients with GS 3 + 4 with and without TGG5 (92 vs. 100%, P = 0.16), as well as between patients with GS 4 + 3 with and without TGG5 (79 vs. 71%, P = 0.30). Similarly, there were no differences in 3-year BCRFS rates between patients with GS 4 + 4 with and without TGG5 (80 vs. 71%, P = 0.38). Conclusions: In our population, the presence of TGG5 in RARP specimens had no strong impact on pathological and prognostic outcomes.